Hydrogen-bonded interpolymer complexes : formation, structure and applications - Khutoryanskiy, Vitaliy V.; Staikos, Georgios (World Scientific Pub. Co., 2009)
Noncovalent interactions play key roles in many natural processes leading to the self-assembly of molecules with the formation of supramolecular structures. One of the most important forces responsible for self-assembly is hydrogen bonding, which also plays an important role in the self-assembly of synthetic polymers in aqueous solutions. Proton-accepting polymers can associate with proton-donating polymers via hydrogen bonding in aqueous solutions and form polymer-polymer or interpolymer complexes. There has been an increased interest among researchers in hydrogen-bonded interpolymer complexes since the first pioneering papers were published in the early 1960s. Several hundred research papers have been published on various aspects of complex formation reactions in solutions and interfaces, properties of interpolymer complexes and their potential applications. This book focuses on the latest developments in the area of interpolymer complexation via hydrogen bonding. It represents a collection of original and review articles written by recognized experts from Germany, Greece, Kazakhstan, Poland, Romania, Russia, UK, Ukraine, and the USA. It highlights many important applications of interpolymer complexes, including the stabilization of colloidal systems, pharmaceuticals, and nanomaterials.